Issues of confidentiality and privacy of data with relation to HIV - Korff, Douwe (AIDS Action Europe, 2007)
Presentation at a (UK) National Aids Trust and Aids Action Europe seminar on Legislation and judicial systems in relation to HIV and AIDS (Friday 20 April 2007)